Longitudinal study of a mouse model of familial porphyria cutanea tarda - Arch, D D; Bergeron, Michel; Hathaway, L; Kushner, J P; Phillips, J D; Franklin, M R (Cellular and Molecular Biology, 2009)
Most rodent models of porphyria cutanea tarda (PCT) share in common the administration of iron and agents that induce transcription of cytochrome P450s. Dissection of changes related to porphyrin accumulation required generation of a genetic model free from exogenous precipitants. Mice heterozygous for a null Urod mutation and homozygous for null Hfe alleles spontaneously develop major increases in hepatic and urinary porphyrins several months after weaning but the high % uroporphyrin signature of PCT is established earlier, before total hepatic and urinary porphyrins rise. Total porphyrin levels eventually plateau at higher levels in females than in males. Porphyrinogens were the dominant tetrapyrroles accumulating in hepatocytes. Hepatic Urod activity is markedly reduced but total hepatic heme content does not diminish. Microsomal heme, however, is reduced and in vitro metabolism of prototype substrates showed that some but not all cytochrome P450 activities are reduced. High hepatic levels of uroporphyrinogen are also associated with increased glutathione S-transferase activity and elevated mRNA of 2 transporters, Abcc1 and Abcc4. This murine model of familial PCT affords the opportunity to study changes in porphyrinogen and porphyrin accumulation and transport in the absence of exogenous factors that alter P450 activity and transmembrane transporters.